PENDAMPINGAN PETANI USAHA GARAM TRADISIONAL PADA KOPERASI TASIK SEGARA LESTARI DI DESA LES, KECAMATAN TEJAKULA, KABUPATEN BULELENG - I Wayan Rideng; I Ketut Kasta Arya Wijaya; Ni Made Wahyuni (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
One of the traditional agricultural commodities in Bali, one of which is the salting business which is carried out traditionally. To carry out the salting business, coastal area land is needed. One of its areas that has a fairly long beach area is in Les Village, Tejakula District, Buleleng Regency. The development of salt business carried out by people who are members of petan groups is traditional. These salt farmers, are a livelihood that is passed down in decline. To be able to maximize the salting business, a cooperative has been formed which is named the Tasik Segara Lestari Cooperative. The members of the cooperative are farmers or groups of farmers in the traditional salting business in Les Village. The Tasik Segara Lestari Cooperative, which was formed in 2016, has not been able to optimally perform services to its members. Among them, it has not been able to provide capital strengthening for existing groups, the lack of facilitation in marketing production products, access to capital to financial institutions, and improving technology in providing assistance in improving processing, and also not optimal synergy with government officials with official villages (Perbekel).